Diagnostic features of multiple organic system disorders associated with COVID-19 in a child of primary school age - S. G. Fetisova; A. Ya. Starshinova; O. A. Kofeynikova; A. A. Starshinova; E. S. Sheyanova; T. L. Vershinina; A. V. Ryzhkov; A. Yu. Skripnik; T. M. Pervunina; E. S. Vasichkina (Журнал инфектологии, 2023)
The advent of the COVID-19, specialists are increasingly encountering previously unknown pathological conditions in their practice. For some time, we have believed that COVID-19 in children is most often mild and asymptomatic. However, with the passage of time and the accumulation of the experience, it became obvious that the new infectious disease it will be quite severe in children. Differential diagnosis of multiple organ disorders in children during the COVID-19 pandemic should be primary carried out with the Multisystem Inflammatory Syndrome in Children, associated with COVID-19 (MIS-C), as well as Long-COVID-19. According to published data, the manifestations of these conditions are due to frequent lesions of the gastrointestinal tract (60–100 %), cardiovascular (80 %), nervous (29–58 %) and respiratory (21–65 %) systems. At present, there is no exact idea of these pathological conditions, the criteria for their diagnosis and the tactics of managing children, not only at the stage of diagnosis, but also at the stage of observation. The authors present a diagnostically complex clinical case describing the development of multiple organ damage in a 7-year-old child after contact with a mother who was sick with COVID-19. The data on the course features, the results of the examination and the difficulties of differential diagnosis of this case with other diseases with a similar clinic are summarized.